Factors Affecting the Success of PPP Transport Projects in Vietnam - Kien, Trung Tran; Minh Nguyen, Nguyet (International Journal of Sustainable Construction Engineering and Technology, 2023)
Transport infrastructure plays an important role in the development of each country, especially for developing countries like Vietnam. To promote the development of transport infrastructure as well as to deal with some challenges such as budget and project efficiency, the Public Private Partnership (PPP) model is a very proper choice. The factors that determine the success of PPP transport projects are important issues to be analyzed in different countries. The article aims at identifying the factors and the extent of their influence on the success of PPP transport project in Vietnam. Research data are collected from surveys with questionnaire to capture related partners’ perceptions of success factors. The influence level of the factors is assessed on a 5-point Likert scale (from 1 - very low to 5 - very high). A total of 92 questionnaires were collected and analyzed using Statistical Package for the Social Sciences (SPSS) software to rank the influence of success factors. Research results show that “Adequate and transparent legal framework”, “State and private commitments and responsibilities”, “Transparency in bidding”, “State support policy” and “Good governance” are the top five factors determining the success of a PPP transport project in Vietnam. The new findings of the study help the State and investors better understand the factors determining the success of PPP transport projects in Vietnam in order to make appropriate decisions on policies.